Development of a Matlab Code for Plane Wave Lens and its Validation by Autodyn-2D - Naeem, K.; Hussain, A. (Engineering, Technology & Applied Science Research, 2018)
Plane wave generator is normally composed of two explosives having dissimilar detonation velocity. It is used for directing the spherically outgoing shock wave front to a planar form. Plane wave generators are utilized to find material behavior under dynamic loading. This paper presents the shock arrival time for two plane wave generators by developed Matlab code and its comparison with Ansys Autodyn. The diameter of both plane wave generators is kept the same. One plane wave generator is composed of Octogen and Barium Nitrate and the other is composed of Octogen and Tri Nitro Toluene. Obtained results were surprisingly in agreement. Maximum and minimum obtained flatness for the plane wave were ±0.56 and ±0.08ms respectively within the whole diameter of the plane wave generator. The developed code can be utilized to find the profile of a plane wave generator, minimizing the time and cost many times.